Incomplete Retinal Pigment Epithelial and Outer Retinal Atrophy in Age-Related Macular Degeneration: Classification of Atrophy Meeting Report 4 - Guymer, Robyn H; Rosenfeld, Philip J; Curcio, Christine A; Holz, Frank G; Staurenghi, Giovanni; Freund, K Bailey; Schmitz-Valckenberg, Steffen; Sparrow, Janet; Spaide, Richard F; Tufail, Adnan; Chakravarthy, Usha; Jaffe, Glenn J; et al. (Ophthalmology (Rochester, Minn.), 2020)
To describe the defining features of incomplete retinal pigment epithelium (RPE) and outer retinal atrophy (iRORA), a consensus term referring to the OCT-based anatomic changes often identified before the development of complete RPE and outer retinal atrophy (cRORA) in age-related macular degeneration (AMD). We provide descriptive OCT and histologic examples of disease progression. Consensus meeting. Panel of retina specialists, including retinal imaging experts, reading center leaders, and retinal histologists. As part of the Classification of Atrophy Meeting (CAM) program, an international group of experts analyzed and discussed longitudinal multimodal imaging of eyes with AMD. Consensus was reached on a classification system for OCT-based structural alterations that occurred before the development of atrophy secondary to AMD. New terms of iRORA and cRORA were defined. This report describes in detail the CAM consensus on iRORA. Defining the term iRORA through OCT imaging and longitudinal cases showing progression of atrophy, with histologic correlates. OCT was used in cases of early and intermediate AMD as the base imaging method to identify cases of iRORA. In the context of drusen, iRORA is defined on OCT as (1) a region of signal hypertransmission into the choroid, (2) a corresponding zone of attenuation or disruption of the RPE, and (3) evidence of overlying photoreceptor degeneration. The term iRORA should not be used when there is an RPE tear. Longitudinal studies confirmed the concept of progression from iRORA to cRORA. An international consensus classification for OCT-defined anatomic features of iRORA are described and examples of longitudinal progression to cRORA are provided. The ability to identify these OCT changes reproducibly is essential to understand better the natural history of the disease, to identify high-risk signs of progression, and to study early interventions. Longitudinal data are required to quantify the implied risk of vision loss associated with these terms. The CAM classification provides initial definitions to enable these future endeavors, acknowledging that the classification will be refined as new data are generated.